WebGIS Application of Geospatial Technology for Tourist Destination in Malang - Firmansya, Dafid Bayu; Ramdani, Fatwa; Tolle, Herman (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Tourism is a place of relaxation for people in which they can plan their sights based on Information. GIS-based information is increasingly important among tourists as it allows them to get to know places, and this has a deep appeal for travel planning. Malang is a famous tourist destination in Indonesia. The region is visited by a large number of tourists from various parts of the world each year. The number of tourists visiting Malang from year to year is always increasing by considering the number of tourism potential in Malang. However, in the absence of a Tourist Information System, tourists face various difficulties in finding various tourism information. Geospatial technology has changed every area of life and the tourism industry cannot be excluded. The purpose of this research is to develop an interactive and easy-to-use Geographic Information System (GIS) that enables tourists to get information about tourism objects. This research actively demonstrates the potential application of geospatial technology to explore tourist destinations with some detailed information.